Un modelo para el control de inventarios utilizando dinámica de sistemas (Estudios) - Samaniego Guevara, Hernán (2019)
The administrative model, for management in inventory control designed and applied in a productive company, in order to potentiate its development using the dynamics of systems methodology, facilitates to visualize possible results according to the applied strategies. The article aims to apply, depending on the specific needs of the study case, specific variables for the inventory process. For this purposes, system dynamics were used in inventory management, using 56 inputs that are part of the inventory and 18 variables. The main results aim to a higher production than the inventory level, whose adjustment to reach the optimum level implies the purchase of 2,500 units, causing the rising of total cost. The proposed model will allow to generate further studies based on the inventory management of the company since it is possible to analyze the dynamic behavior of this system, incorporating variables that strengthen business operations.